2013
DOI: 10.1089/neu.2013.2910
|View full text |Cite
|
Sign up to set email alerts
|

Dose- and Time-Dependent Neuroprotective Effects of Pycnogenol® following Traumatic Brain Injury

Abstract: After traumatic brain injury (TBI), both primary and secondary injury cascades are initiated, leading to neuronal death and cognitive dysfunction. We have previously shown that the combinational bioflavonoid, PycnogenolÒ (PYC), alters some secondary injury cascades and protects synaptic proteins when administered immediately following trauma. The purpose of the present study was to explore further the beneficial effects of PYC and to test whether it can be used in a more clinically relevant fashion. Young adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 63 publications
1
36
0
Order By: Relevance
“…Our results of early heterogeneous up-regulation of both the M1 and M2 phenotypes suggest that an early time post injury is a very important factor to consider when investigating a therapeutic window. Our previous studies also showed that oxidative stress in the cerebral tissue occurs as early as 3 h post TBI [4][5][6]. The superoxide producing enzyme (NADPH-oxidase), a known contributor of inflammation and oxidative-stress mediated neurodegeneration [21,64] is up-regulated within 6 h after neurotrauma [7].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our results of early heterogeneous up-regulation of both the M1 and M2 phenotypes suggest that an early time post injury is a very important factor to consider when investigating a therapeutic window. Our previous studies also showed that oxidative stress in the cerebral tissue occurs as early as 3 h post TBI [4][5][6]. The superoxide producing enzyme (NADPH-oxidase), a known contributor of inflammation and oxidative-stress mediated neurodegeneration [21,64] is up-regulated within 6 h after neurotrauma [7].…”
Section: Discussionmentioning
confidence: 89%
“…The superoxide producing enzyme (NADPH-oxidase), a known contributor of inflammation and oxidative-stress mediated neurodegeneration [21,64] is up-regulated within 6 h after neurotrauma [7]. The pro-inflammatory cytokine's up-regulation at 48 h [71] and significant loss of synaptic components at 96 h [6] support that "time-post-injury" is an important factor in developing therapeutic strategies after TBI.…”
Section: Discussionmentioning
confidence: 99%
“…A second study reported similar or further declines in pre- and postsynaptic proteins 96 h after a cortical impact depth of 2 mm was produced by a 5-mm impactor tip (Ansari et al, 2013). In contrast, it is noteworthy that a more moderate level of cortical impact injury (0.5-mm impact depth with a 3-mm impactor) resulted in 40–50% increases in synaptophysin in the ipsilateral hippocampus 48–72 h post-impact (Thompson et al, 2006).…”
Section: Discussionmentioning
confidence: 91%
“…Pycnogenol ® has a beneficial effect on the synaptic proteins of rats with brain injuries. In 2013, Ansari et al (10) found that Pycnogenol ® , administered after a brain contusion, led to a reduction in the intensity of brain injury in young adult rats. Norris et al (15) found that Pycnogenol preserved CA3-CA1 synaptic functions in rats with traumatic brain injuries and suggested that Pycnogenol ® may have a therapeutic role in traumatic brain injuries in humans.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of this knowledge, antioxidant-mediated prevention of the secondary injury cascade caused by mediumintensity head trauma has recently drawn significant attention (9). Ansari et al (10) showed that Pycnogenol ® , an antioxidant made of pine bark extract, demonstrated some neuroprotective properties in traumatic brain injury. In this study, we investigated the effect of Pycnogenol ® on spatial learning and memory (SLM) function in rats subjected to experimental low-to-moderate intensity closed head injury.…”
Section: Introductionmentioning
confidence: 99%